Wombs, Wizards, and Wisdom: Bilbo's Journey from Childhood in The Hobbit - Rory W Collins (Crossing Borders: A Multidisciplinary Journal of Undergraduate Scholarship, 2020)
In The Hobbit, J. R. R. Tolkien constructs middle-aged Bilbo Baggins as a sheltered and emotionally immature ‘child’ during the opening chapters before tracing his development into an autonomous, self-aware adult as the tale progresses. This article examines Tolkien’s novel qua bildungsroman through both a literary lens—considering setting, dialogue, and symbolism, among other techniques—and via a psychological framework, emphasizing an Eriksonian conception of development. Additionally, Peter Jackson’s three-part film adaptation of The Hobbit is discussed throughout with ways that Jackson succeeds and fails at portraying Bilbo’s childlike attributes noted. I argue that Tolkien presents a sophisticated account of Bilbo’s childish persona growing into a mature adult worldview, and that Jackson appropriately reflects much, though not all, of this development in his films.
Keywords: The Hobbit; J. R. R. Tolkien; literature; fantasy; film; psychology; psychoanalysis; development; Erik Erikson